The Potential of Tepache Drinks with Addition of Guava Skin as Probiotic Drink - Afrinia Eka Sari; maulin Inggraini; Arindah Nur Sartika (Journal of Global Nutrition, 2026)
The development of probiotic beverage innovation is now growing. Probiotic products are in demand by the public because of their benefits in maintaining digestive track Health. One drink that has potential to be a probiotic drink is tepache, a fermented drink made from pineapple skin dissolved in a sugar solution. The fermentation process that occurs produces lactic acid bacteria that have potential to be probiotics. In this study, an experimental design was used where tepache drinks were made with six different formulas, where the differences are found in the types of sugar, namely palm sugar and granulated sugar, and the amount of sugar added: F1 (16%), F2 (22%) anf F3 (27%) is the same for added brown sugar in F4, F5, F6. Identification of bacteria was carried out by growing on PCA (Plate Count Agar) media to determine the Total Colony Count and MRSA (de Mann Rogosa Agar) media to grow lactic acid bacteria in this case selectively in the grow of lactobacillus. From the results of observations for 3 days, showed that bacteria grew on PCA media at a dilution 10-4, 10-5, and 10-6 and on MRSA media grew at a dilution of 10-4. From the pH measurements, the results obtained for all formulas were pH 4 and brix degress 60. Organoleptic test showed that this tepache drink was liked by panelists, data taken from 20 panelist because its refreshing, sour taste and fruity aroma.The study concluded that tepache has the potential to be a probiotics beverage, as the bacteria found to grow were lactic acid bacteria with pH that matches the probiotic drink and was preffered by panelists